2016
DOI: 10.1111/dom.12682
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in GLP1R gene is associated with the glycaemic response to treatment with gliptins

Abstract: Gliptins act by increasing endogenous incretin levels. Glucagon-like peptide-1 receptor (GLP1R) and glucose-dependent insulinotropic peptide receptor (GIPR) are their indirect drug targets. Variants of GLP1R and GIPR have previously been associated with the incretin effect. The aim of the present pilot study was to examine associations of the GLP1R and GIPR gene variants with the glycaemic response to gliptins. A total of 140 consecutive patients with type 2 diabetes were followed-up 6 months after initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 15 publications
2
29
0
2
Order By: Relevance
“…Previous studies showed that polymorphism in DPP4 [25, 26] and GLP1R [27, 28], which are directly involved in the mechanism of action of DPP-4 inhibitors, was associated with the glycemic response to DPP-4 inhibitor treatment. Appropriate regulation of insulin secretion may also be related to DPP-4 inhibitor efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that polymorphism in DPP4 [25, 26] and GLP1R [27, 28], which are directly involved in the mechanism of action of DPP-4 inhibitors, was associated with the glycemic response to DPP-4 inhibitor treatment. Appropriate regulation of insulin secretion may also be related to DPP-4 inhibitor efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genetic variations among different ethnic groups may alter the metabolism and therapeutic response of DPP-4 inhibitors, as previously demonstrated by pharmacogenomic and pharmacogenetic studies [23, 24]. Accordingly, the genetic effects of several genes such as DPP4 [25, 26], GLP1R [27, 28], and TCF7L2 [29] on the therapeutic response of DPP-4 inhibitors in patients with T2D have been investigated in clinical trial and case-control studies with a candidate gene approach. In the present report, we used an assumption-free genome-wide association study (GWAS) to identify the potential genes involved in the therapeutic response to DPP-4 inhibitors among patients with T2D in a Taiwanese population.…”
Section: Introductionmentioning
confidence: 99%
“…The risk C allele was also reported to be associated with higher fasting glucose but lower 2‐h postload glucose concentrations during an OGTT . Taken together, these findings suggest that GIPR variants could potentially modulate the response to DPP‐4 inhibitors, nevertheless, to date, this effect has not been revealed by clinical studies …”
Section: Summary Of the Literaturementioning
confidence: 95%
“…The polymorphism rs10305493 (Ser333Cys) instead has been proven to preserve peptide response . The SNP rs6923761 (Gly168Ser) was nominally associated with reduced insulin secretion in response to GLP‐1 infusion during a hyperglycemic clamp in nondiabetic American subjects and with a weaker response to the glucose‐lowering effect of DPP‐4 inhibitors in patients with T2DM . On the contrary, the same polymorphism was associated with higher efficacy of liraglutide, and it was shown to increase weight and fat mass loss after liraglutide treatment, different types of diet, or bilio‐pancreatic diversion surgery .…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation